Kesan Perbedaan Beribadah yang Dirasakan Santri Berlatarbelakang Muhammadiyah di Pondok Pesantren NU Selama Bulan Ramadan: Studi Kasus Pondok Pesantren Darul Abror dengan Pendekatan Fenomenologi Agama - Sekar Arum Pramusti; Sinaga Fajri Subhaan Syah (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2023)
This type of research is field research with a descriptive qualitative model, which uses a phenomenological approach to religion. The purpose of this study was to find out some of the fundamental differences between Nahdlatul Ulama (NU) culture and Muhammadiyah culture in the month of Ramadan and find out what the impressions of female students with Muhammadiyah backgrounds are in Islamic boarding schools with NU backgrounds. This study used an in-depth interview method with informants, namely several female students with Muhammadiyah backgrounds at the Darul Abror Islamic Boarding School. The formulation of the problem raised in this study is about the differences felt during the month of Ramadan at the Darul Abror Islamic Boarding School and regarding the impressions felt while they were there. The results of the study showed that there were some fundamental differences that were felt by the female students starting from the start of their fast, the number of cycles of tarawih prayer, the answers to the Bilal reading, and the use of the qunut prayer in the witr prayer which began on the 16th night of Ramadan.